THE SYSTEMIC FUNCTIONAL LINGUISTICS: THE APPROPRIATE AND INAPPROPRIATE USE OF DEVICES IN STUDENTS’ ACADEMIC TEXT - Arianto, Muhammad Affandi; Refnaldi, Refnaldi; Rosa, Rusdi Noor (English Department FBS UNP, 2016)
This qualitative research was conducted to describe the types of grammatical cohesive devices and to compare the frequency of using the appropriate and inappropriate of those devices used by students in composing analytical exposition text. The subjects of this research were chosen conveniently by selecting only 34 students of grade two of SMAN 7 Padang. The data was collected from the analytical exposition texts written by them.Â The result of this research shows that the students are able to use the grammatical cohesive devices in variant ways. Those four types found are reference, conjuction, ellipsis, and substitution. Reference and conjuction were found most frequent in studentsâ€™ texts with the percentage of occurring those types were 62.77% and 31.88%. In adition, ellipsis dan substitusition, each of them gives contributes to students texts just 4.8% and 0.55%. Students tend to use the inappropriate pronoun reference when they try to refer between the subject and object in their sentences. Of 1104 times of using the devices, the most inappropriate use was located in using reference. The frequency of using these inapprorate references was 88 times.